Reference in Filipino bilingual children's oral narratives in English - Yuan, Cao (Animo Repository, 2010)
This paper aimed to provide insights into the development of children's ability in establishing character references during their story production in English and in using pronominal reference strategies for maintaining and switching character references. Audiotaped interviews were applied between 40 bilingual English-Filipino children with two different age groups: 6-7 and 9-10. Results showed that, overall, there is an increase in frequency of introducing characters with noun phrase at age 6-7 and another more sharp increase from 7-10. In using pronominal reference strategies for maintaining and switching character references, 25% of the 6-7 year olds adopt confused and nominal strategies which are rarely used by those 9-10 years. The 6-7 year old children use advanced anaphoric strategy the same as the 9-10 years but 20% more the latter group deploy indeterminable strategy. Thematic-subject strategy was more applied for the younger group than for the older group; however, it appears much weaker than those of Karmiloff-Smith's (1981, in Shapiro & Hudson, 1991) with only 25% of the 6-7 years applying this strategy. It was suggested that the nature of the materials used to elicit the narratives can influence the conclusions drawn from the results. Further research may include the use of other stories or other narrative genre to investigate children's use of cohesive devices.